Simplify and show work for the following

a) (8ab^7)(-7a^-5b^2)

b) (4y)^2 (3y^3)

c) (2x)^5(3x)^2

Simplify and show work for the following

a) (8ab^7)(-7a^-5b^2)

b) (4y)^2 (3y^3)

c) (2x)^5(3x)^2

Tutors, please sign in to answer this question.

Westford, MA

a) (8ab^7)(-7a^-5b^2)

= (8*(-7))a^(1-5)b^(7+2) = -56a^(-4)b^(9) = -56b^9/a^4

b) (4y)^2 (3y^3)

= 3*4^2y^2y^3 = 48y^(2+3) = 48y^5

c) (2x)^5(3x)^2

= 2^5 x^5 3^2 x^2 = 32*9 x^(5+2) = 288x^7

Mark D.

Quantitative research SPECIALIST with academic/professional experience

New York, NY

5.0
(148 ratings)

John P.

Tutor of math and physics, recent college graduate

Short Hills, NJ

5.0
(21 ratings)

- Math Help 5395
- Math 9728
- Algebra 5026
- Math Help For College 1389
- Algebra Help 965
- Exponents 188
- Algebra 2 3444
- Trigonometry 1512
- Simplifying Expressions 135
- Algebra 1 4034